Recent advances in nanotechnology-based diagnosis and treatment of bladder cancer: an updated review - Keyao Hu; Yanfang Cui; Ning Li; Peng Li; Xiaofei Wang; Jianfeng Chu (International Journal of Smart and Nano Materials)
Bladder cancer, the ninth most prevalent cancer, is difficult to diagnose and cure. Cystoscopy and urine cytology are used to diagnose bladder cancer, but they are invasive, expensive, and insensitive to early-stage cancers. Surgery, chemotherapy, and immunotherapy for bladder cancer are limited by systemic toxicity, drug resistance, and high recurrence rates. Thus, nanotechnology has revolutionized these issues with novel solutions. Nanoparticles’ physicochemical qualities improve MRI and fluorescence imaging sensitivity and specificity. Gold nanoparticles and quantum dots can visualize bladder cancer biomarkers in real time, making them promising functionalized nanoparticles for early detection of bladder cancer. Liposomes, polymeric nanoparticles, and dendrimers act as nanocarriers to deliver chemotherapeutic drugs targeted, regulated, and sustainably, decreasing systemic side effects and boosting therapeutic efficacy. Nanotechnology-driven immune checkpoint inhibition and nanovaccines boost anti-tumor immunity. Theranostic systems combine diagnostic and therapeutic functions into a single system for real-time monitoring and individualized response. This review discusses recent nanotechnology advances in heteranostics and theranostics for bladder cancer detection and therapy, and their ability to overcome current limits. However, nanoparticle biocompatibility, scalability, and control issues persist. The mainstreaming of nanotechnology in bladder cancer management requires interdisciplinary collaboration and research innovation to overcome these limitations and improve patient outcomes and precision medicine.